HYBRID WIRELESS BATTERY CHARGING OF ELECTRIC VEHICLE - Prof. Mulla T. Y.; Mr. Mahibub Shaikh; Ms. Shubhangi Kargule; Mr. Saurabh Navale; Ms. Aasawari Gaikwad (International Journal of Innovations in Engineering Research and Technology, 2023)
In this conservation of energy is the most necessary part of the society and as automobile is an important part of society in day to day life, hence the conservation of energy well as pollution due to the use of Bio-fuels in automobile sector is a challenging job. So energy conservation and pollution free vehicle became most important factor. To solve this issue the concept of Electric Vehicle (EV) (electricity powered automobile) system was introduced, this can be used in all type of automobile such as cars, bus, etc. But once the battery of EV is charged it travels a limited distance ,again we have to charge the battery of vehicle, which is a time consuming process. In this paper we worked on this issue of electrical Vehicle (EV). We resolved this by doing wireless charging alternating charge the battery .This will helps to improve the distance covering rang of electrical vehicle (EV) and make it more efficient. It will save the lot of time which is needed to charge the electric vehicle (EV).